Mengenal Sejarah Berdirinya Amerika dari Kolonisasi Hingga Kemerdekaan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This journal comprehensively examines the history of the United States from European colonization to independence in 1776. The investigation begins with the arrival of Europeans, who first set foot on the American continent and established colonies. The process of establishing these colonies played a crucial role in shaping the social, economic, and political structures of the Americas. Over time, dissatisfaction with perceived oppressive British rule sparked revolutionary struggles. These tensions culminated in events such as the Boston Rebellion and the imposition of unwanted taxes. This struggle ultimately led to the Declaration of Independence in 1776, which declared America's independence from Britain. This transformation from the Thirteen Colonies into an independent nation upholding the principles of liberty and popular sovereignty was a significant historical milestone. American independence inspired independence movements in many other countries, exerting a significant influence on the development of world history. Furthermore, this struggle also introduced new concepts in government, such as democracy, human rights, and government based on popular consent, which became the foundation of modern political systems in many countries. The struggle proved that the people have the power to overthrow tyranny and build a nation based on the principles of justice and freedom.